Addiction Treatment with Deaf and Hard of Hearing People: An Application of the CENAPS Model. Issue 3 (2nd October 2017) - Yates, Leo; Dreany-Pyles, Laura
ABSTRACT: Alcohol and drug addiction is a significant problem among deaf and hard of hearing people. Looking through a Deaf culture lens, treatment for alcohol and drug addiction is key for providing care for deaf and hard of hearing clients. Using the CENAPS model, an applied cognitive-behavioral therapy program is recommended for addiction treatment. The CENAPS model provides clinicians with tools for stabilizing deaf and hard of hearing clients, supporting their transition to early recovery. Educating the client about the stages of relapse and the stages of recovery, clinicians using this model can better treat and prepare deaf and hard of hearing clients for long-term recovery.